Comparative Study of Micro-Leakage Between Glass Ionomer Cement Restoration Materials and Alkasites on Cavitas Class I (GV. Black) - Viona DIANSARI; Diana Setya NINGSIH; Sri FITRIYANI; Iin SUNDARI; Subhaini SUBHAINI; Muhammad Kahlil GIBRAN (Dentistry Faculty, 2022)
Microleakage is a gap that allow clinically undetectable passage of bacteria, fluids, chemical substances between the tooth and its restoration. Microleakage can occurs whether in a cavity restored with Glass Ionomer Cement or Alkasite. The objective of this study is to compare the microleakage between GIC and Alkasite after 1 day, 7 days and 30 days polymerization. This study used 30 specimens divided into six groups. Group A is restored with GIC and Group B restored with Alkasite. Group A1 and B1 restored and conditioned in incubator for 1 day, group A2 and B2 for 7 days, group A3 and B3 for 30 days. The specimens isolated using varnish nail except the restored area and immersed in methylene blue 1% for 1 day, then all specimens were washed and cut longitudinally. The results were observed using a stereomicroscope. The observation results analyzed using nonparametric test Kruskal-Walis test, showed theres no significant difference in each material with differentconditioning times (p 0.05). Post hoc test using Mann-Whitney likewise, showed no significant difference between GIC and Alkasite with similar conditioning time. Descriptive statistics showed that all the mean of microleakage in GIC is bigger than Alkasite and microleakage mean score in both materials conditioned for 30 days in incubator is smaller than conditioned for 1 day and 7 days. This study concluded that microleakage in Alkasite is smaller than Glass Ionomer CementKEYWORDS: Microleakage, Glass Ionomer Cement, Alkasite, Class I